2012
DOI: 10.1111/sms.12015
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable influence of structured exercise program on total leisure‐time physical activity

Abstract: In randomized controlled trials (RCTs), with customized structured physical exercise activity (SPEA) interventions, the dose of leisure-time physical activity (LTPA) should exceed the LTPA dose of the nonexercising control (C) group. This increase is required to substantiate health improvements achievable by exercise. We aimed to compare the dose of SPEA, LTPA, and total LTPA (SPEA + LTPA) between a randomized Nordic walking (NW) group, a power-type resistance training (RT) group, and a C group during a 12-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…,b; Wasenius et al. ), however, this is the first investigation of skeletal muscle tissue from that intervention study.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…,b; Wasenius et al. ), however, this is the first investigation of skeletal muscle tissue from that intervention study.…”
Section: Resultsmentioning
confidence: 97%
“…,b; Wasenius et al. ). The participants were recruited through occupational healthcare services located in Southern Finland and through newspaper advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Wasenius and colleagues [12] demonstrated no significant increase in total leisure time physical activity with either a Nordic walking or resistance training exercise intervention compared to a control group. While Wasenius et al also used a randomised controlled trial design with two different interventions, there were several key methodological differences to the current study.…”
Section: Discussionmentioning
confidence: 96%
“…The results of this review suggested that there is conflicting evidence as to the existence of an activitystat with 63, 40 and 80 % of studies involving children, adult and older adult studies respectively, reporting evidence of compensation in either physical activity or energy expenditure [11]. Several experimental papers investigating compensation have been published since this review [1221], and similarly report conflicting results. In children and adults, several recent studies have shown some evidence of compensation with an imposed exercise stimulus [1215], however there are at least as many that demonstrate no evidence of an activitystat or compensatory effect [1619].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation